CSR and Profitability as Determinants of Firm Value: Evidence from Sri-Kehati Index - Ono Tarsono; Maya Mustika; Fasya Nabila Salim; Dwi Windu Suryono (Research of Business and Management, 2026)
This study aims to investigate the impact of Corporate Social Responsibility (CSR) and profitability on firm value among companies listed on the Sri-Kehati Index of the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A descriptive quantitative research design was applied using panel data analysis with EViews 12. The population consisted of firms listed on the Sri-Kehati Index, with purposive sampling selecting 11 companies, resulting in 44 firm-year observations. Secondary data were collected through documentation from the official IDX website (www.idx.co.id). The results reveal that CSR has a negative and significant effect on firm value, while Return on Assets (ROA) and Return on Investment (ROI) do not have a significant effect. These findings suggest that while CSR initiatives significantly shape firm value, profitability indicators such as ROA and ROI may not directly drive market valuation in Sri-Kehati Index firms.